Feeling Good and Functioning Well: Role of Psychological well-being and Perceived Organizational Support in fortifying Commitment - Verma, Anand; Sengupta, Santoshi; Kumar Saini, Ajay (International Journal of Psychosocial Rehabilitation, 2024)
The importance of organizational commitment, i.e. the relative strength of an individual’s identification with and involvement in his organization, is well-established both in theory and in practice. This paper reviews the literature on organizational commitment; evaluates its established relationships with perceived organizational support, work engagement and psychological well‐being; and proposes a conceptual framework in which the effect of work engagement on organizational commitment is moderated by the extent to which an employee perceives organizational support. We propose that perceived organizational support helps realize the benefits of work engagement by fostering psychologicalwell‐being.Thus,itisthefeelgoodfactorofanemployeethatmakes her/him function well and forlong with her/his organization.